THE EFFECTIVENESS OF GOVERNMENT POLICY FOR MSMEs IN SUPPORTING THE NATIONAL ECONOMIC RECOVERY IN JEMBER DISTRICT - Nely Supeni; Mustofa Mustofa; Mainatul Ilmi; Diana Dwi Astuti (MBA - Journal of Management and Business Aplication, 2022)
This research is entitled Effectiveness of Government Policy for MSMEs in Supporting NationalEconomic Recovery in Jember Regency. The purpose of this study was to determine whether theMSME Direct Cash Assistance (BLT) program in Jember Regency was effective and on target?This type of research is qualitative research, with 2 types of data used, namely primary data andsecondary data. The total population is 1330 MSMEs and the sample used is 200 MSMEs.Analysis of the data used is descriptive qualitative analysis. The results of the study show thatthe Government's Policy for MSMEs in Supporting National Economic Recovery in the form ofthe MSME Direct Cash Assistance (BLT) program in Jember Regency has been effective, thiscan be seen from the three indicators used in the study, namely timeliness, accuracy in makingchoices. , and target accuracy. Based on these three indicators, it shows that the BLT MSMEDirect Cash Assistance program in Jember Regency is on time, has made the right choice, and isright on target.